Impact of Na(+)-Translocating NADH:Quinone Oxidoreductase on Iron Uptake and nqrM Expression in Vibrio cholerae - Agarwal, Shubhangi (J Bacteriol, 2020)
The Na(+) ion-translocating NADH:quinone oxidoreductase (NQR) from Vibrio cholerae is a membrane-bound respiratory enzyme which harbors flavins and Fe-S clusters as redox centers. The NQR is the main producer of the sodium motive force (SMF) and drives energy-dissipating processes such as flagellar rotation, substrate uptake, ATP synthesis, and cation-proton antiport. The NQR requires for its maturation, in addition to the six structural genes nqrABCDEF, a flavin attachment gene, apbE, and the nqrM gene, presumably encoding a Fe delivery protein. We here describe growth studies and quantitative real-time PCR for the V. cholerae O395N1 wild-type (wt) strain and its mutant Δnqr and ΔubiC strains, impaired in respiration. In a comparative proteome analysis, FeoB, the membrane subunit of the uptake system for Fe(2+) (Feo), was increased in V. cholerae Δnqr. In this study, the upregulation was confirmed on the mRNA level and resulted in improved growth rates of V. cholerae Δnqr with Fe(2+) as an iron source. We studied the expression of feoB on other respiratory enzyme deletion mutants such as the ΔubiC mutant to determine whether iron transport is specific to the absence of NQR resulting from impaired respiration. We show that the nqr operon comprises, in addition to the structural nqrABCDEF genes, the downstream apbE and nqrM genes on the same operon and demonstrate induction of the nqr operon by iron in V. cholerae wt. In contrast, expression of the nqrM gene in V. cholerae Δnqr is repressed by iron. The lack of functional NQR has a strong impact on iron homeostasis in V. cholerae and demonstrates that central respiratory metabolism is interwoven with iron uptake and regulation. IMPORTANCE Investigating strategies of iron acquisition, storage, and delivery in Vibrio cholerae is a prerequisite to understand how this pathogen thrives in hostile, iron-limited environments such as the human host. In addition to highlighting the maturation of the respiratory complex NQR, this study points out the influence of NQR on iron metabolism, thereby making it a potential drug target for antibiotics.